’n Regsvergelykende blik op die diensverhouding van ’n predikant - Van Coller, Helena E (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The contract of employment and employment relationships of ministers: a comparative view For any party, including a minister, a contract of employment is necessary for purposes of establishing an employment relationship in order to be subject to the Labour Relations Act. If no such employment relationship exists, the court will have no jurisdiction to entertain a dispute in terms of Labour Law. The right to freedom of religion, as contained in the Constitution, allow religious organisations and churches to give meaning to and to define the various positions in the church, including the position of minister according to their own religious views. With reference to some comparative views and the different views within the Dutch Reformed Church, Reformed Church and Anglican Church, there seems to be no general rule as to whether a Minister of Religion is an employee or not and different denominations have different teachings and ideologies. Each individual case will therefore be judged on its own merits and facts. This view is also in line with the approach taken in the Netherlands. The courts must therefore be sensitive to the sui generis nature of churches and should not impose specifc legal or labour relationship onto churches if it is in conflict with their own religious views.